2018
DOI: 10.1039/c8cp02643b
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between H-bonded [CuII3(μ3-OH)] triangles; a combined magnetic susceptibility and EPR study

Abstract: The X-ray crystal structure of the CuII complex [Cu3(μ3-OH)(μ-pz)3(PhCOO)3]- (pz- = pyrazolato anion) shows an isosceles triangular core, further forming a hexanuclear H-bonded aggregate. Cleavage of the H-bonds in solution results in isolated trinuclear species. Analysis of variable temperature magnetic susceptibility data of a powder sample shows an antiferromagnetically-coupled Cu3-core with a doublet ground state and isotropic exchange parameters (Jave = -355 cm-1, Hiso = -JijSiSj). The fitting of magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 77 publications
5
22
0
Order By: Relevance
“…The solid-state structure is characterized by a network of possible dipolar interactions along the chains formed by the trinuclear and mononuclear complexes previously described ( Figure S5). Depending on their magnetic symmetry, i.e., |J| > |J′| versus |J| < |J′|, the spin densities of the triangles may be spread out over all three metal sites, or concentrated on one of them, respectively [13]. Our tentative conclusion from DFT calculation points toward the former case, which is also consistent with the magnetic susceptibility analysis, negating the applicability of the point-dipole approximation and hindering a straightforward analysis of dipolar interactions.…”
Section: Epr Spectroscopy Of (1)supporting
confidence: 67%
See 1 more Smart Citation
“…The solid-state structure is characterized by a network of possible dipolar interactions along the chains formed by the trinuclear and mononuclear complexes previously described ( Figure S5). Depending on their magnetic symmetry, i.e., |J| > |J′| versus |J| < |J′|, the spin densities of the triangles may be spread out over all three metal sites, or concentrated on one of them, respectively [13]. Our tentative conclusion from DFT calculation points toward the former case, which is also consistent with the magnetic susceptibility analysis, negating the applicability of the point-dipole approximation and hindering a straightforward analysis of dipolar interactions.…”
Section: Epr Spectroscopy Of (1)supporting
confidence: 67%
“…The antiferromagnetic exchange among the Cu II centers of the triangular Cu 3 (µ 3 -O/OH) units has been studied extensively by us and others [7][8][9][10][11][12]. We have recently turned our attention to interactions between weakly-coupled Cu 3 (µ 3 -O/OH) species and shown that the presence of weak dipolar interactions str evident in the magnetic susceptibility and EPR spectra of H-bonded Cu 3 (µ 3 -OH) units [13]. Continuing along the same lines, we report here the structure and magnetochemical studies of a heptanuclear Cu II assembly employing 4-phenyl-pyrazole ligands and of a polymeric structure containing Cu 3 N 6 metallacycles with terminal and bridging azido ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Color coding: Cyan, Cu; blue, N; red, O; black, C; pink, H. Selected interatomic distances (Å) and angles (º): CuCu: 3.350(5)-3.404 (6); Cu-( 3 -OH): 1.979(2)-1.993(2); Cu-N: 1.941(3)-1.930(3); Cu-O(NO): 2.026(3), 2.062(4), 2.141(4); Cu-O-Cu: 115.19(1), 118.28(2).To assess the stability of the complexes in solution, EPR spectra in frozen CH 2 Cl 2 were recorded for 1 and 3 at 4.2 K(Figure 3). Both spectra exhibited similar characteristics typical of antiferromagnetically-coupled half-integer spin triangles experiencing antisymmetric exchange (or Dzyaloshinksii-Moriya) interactions, previously manifested in other complexes of this family 30,34. The spectra of 1(3) consist of an absorption-like peak at g = 2.14(2.18) and a derivative feature at g = 1.87(1.84), with a broad trough centered at g = 1.73(1.74).…”
supporting
confidence: 59%
“…These parameters can also be tailored through molecular design. E.g., properly chosen ligand blends can force a low molecular symmetry that will also be reflected on the magnetic one, as has been shown in copper(II), 46 or iron(III) [47][48][49][50] triangles, with the latter type stabilizing S T = 5/2 ground states in cases of extreme distortions. 49,50 However, this criterion does not necessarily exclude high-symmetry…”
Section: Discussionmentioning
confidence: 97%